Estimasi Ruang Terbuka Hijau di Kota Jambi Tahun 2013 dan 2021 Menggunakan Transformasi NDVI (Normalized Difference Vegetation Index) - Yeri Dwisyawal Aulia; Anis Tatik Maryani; Hutwan Syarifuddin (Universitas Batanghari Jambi, 2023)
Population growth is always followed by an increase in the need for land to be used as residential areas and other supporting facilities. This situation causes pressure on the existence of green open space (RTH). In the period from 2010 to 2021, the population of Jambi City has experienced an average growth of 1.24% per year. Population growth is accompanied by the development of the physical sector to support the needs of the population in Jambi City, so that the green open space area has decreased and turned into a built-up area. This study aims to analyze the distribution of green open space in Jambi City in 2013 and 2021. The analysis used is remote sensing by utilizing Landsat 8 OLI satellite imagery. The area and distribution of green open space is calculated based on the value of vegetation density using the Normalized Difference Vegetation Index (NDVI) method in 2013 covering an area of Â± 11.813,68 hectares, while in 2021 it has decreased to Â± 9.605,39 hectares.